If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5 = 0.5(2x + -7) Reorder the terms: 5 + x = 0.5(2x + -7) Reorder the terms: 5 + x = 0.5(-7 + 2x) 5 + x = (-7 * 0.5 + 2x * 0.5) 5 + x = (-3.5 + 1x) Solving 5 + x = -3.5 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + x + -1x = -3.5 + 1x + -1x Combine like terms: x + -1x = 0 5 + 0 = -3.5 + 1x + -1x 5 = -3.5 + 1x + -1x Combine like terms: 1x + -1x = 0 5 = -3.5 + 0 5 = -3.5 Add '-5' to each side of the equation. 5 + -5 = -3.5 + -5 Combine like terms: 5 + -5 = 0 0 = -3.5 + -5 Combine like terms: -3.5 + -5 = -8.5 0 = -8.5 Simplifying 0 = -8.5 Combine like terms: 0 + 8.5 = 8.5 8.5 = -8.5 + 8.5 Combine like terms: -8.5 + 8.5 = 0.0 8.5 = 0.0 The solution to this equation could not be determined.
| 5(x+11)=5(21-x) | | 54=3(2-2x) | | X*X*Y*Y=1600 | | x+4=0.6(2x-7) | | tn=tn-1+6 | | h(6)ifh(x)=x^2-2x-5 | | 8x+9-7x=11 | | 7(3x-9)=-63 | | B=4m+6 | | 21-6x=9-9x | | tn=tn-1+2 | | x+4=0.5(2x-7) | | 5q+p=q-3 | | 3(7x+9)=48 | | x^2+y^2=1600 | | 7*[3(3)-2]+5=6*[2(3)-1]+24 | | 2cos^2-5cos-3=0 | | 6=-3+33 | | k-15=-30 | | tn=3n-1 | | 9+4x=23 | | 4X+11=2X^2+13X+6 | | -7(-6x+2)=48 | | 5(x+11)=5(12-x) | | 4x+9=-31-4x | | e-6=7 | | tn=tn-1-4 | | 4(-7+2x)=-28 | | 3(3-y)1=31 | | -4x^3+4x^2+35x=0 | | 2-a=3 | | 4x-23x+18x-278=34 |